Cofilin activity downstream of Pak1 regulates cell protrusion efficiency by organizing lamellipodium and lamella actin networks - Delorme, Violaine (2007)
Protrusion of the leading edge of migrating epithelial cells requires precise regulation of two actin filament (F-actin) networks, the lamellipodium and lamella. Cofilin is a downstream target of Rho-GTPase signaling that promotes F-actin cycling through its F-actin nucleating, severing and depolymerizing activity. However, its function in modulating lamellipodium and lamella dynamics, and their implications for protrusion efficiency have been unclear. Using quantitative fluorescent speckle microscopy, immunofluorescence, and electron microscopy, we establish that the Rac1/Pak1/LIMK1 signaling pathway controls cofilin activity within the lamellipodium. Enhancement of cofilin activity accelerates F-actin turnover and retrograde flow, resulting in widening of the lamellipodium. This is accompanied by increased spatial overlap of the lamellipodium and lamella networks and reduced cell edge protrusion efficiency. We propose that cofilin functions as a regulator of cell protrusion by modulating the spatial interaction of lamellipodium and lamella in response to upstream signals.